Rapid separation and identification of 96 main constituents in Huanglian Jiedu decoction via ultra‐high performance liquid chromatography–Orbitrap Fusion Tribrid mass spectrometer. (14th October 2022) - He, Dongmei; Liao, Fengyun; Wang, Peng; Gan, Bing; Yu, Lingling
Abstract: Huanglian Jiedu decoction is a widely used traditional Chinese medicine with a broad spectrum of therapeutic effects, including heat clearing, detoxification, and attenuation of inflammation. However, the composition of Huanglian Jiedu decoction is still unclear due to its complexity and limitations of analytical methods. In this study, we established a fast and reliable analytical method based on ultra‐performance LC–Orbitrap Fusion Tribrid mass spectrometer for high‐speed separation and structural identification of multiple compounds in Huanglian Jiedu decoction. The analysis was carried out using a Hypersil GOLD C18 column (2.1 × 100 mm, 1.9 μm) with gradient elution coupled to a high‐definition mass spectrometer system operating in both positive and negative ESI modes. According to the chromatographic retention time, precise molecular weight, fragment ion peaks, and published data, the main chromatographic peaks were attributed to specific molecules whose chemical structures were determined. In total, 96 components were identified, including 34 flavonoids and their glycosides, 23 alkaloids, 18 organic acids, 13 terpenoids, and 8 miscellaneous compounds. This study revealed the detailed chemical composition of Huanglian Jiedu decoction, which is of great importance for quality control and further pharmacological and mechanistic studies.